Cancer treatment in the extreme elderly: case study of a 100-year-old lymphoma patient. (September 2016) - Gilbar, Peter J; Mutsando, Howard; Richmond, Joshua P; Middleton, Ronald B
Limited data are available on the treatment of older adults with cancer. Comorbidities may preclude the administration of effective therapies, particularly in the extreme elderly. Comprehensive geriatric assessment can identify specific weaknesses of the patient and predict unexpected toxicities, thus enabling an optimized treatment strategy in this population. We report a case of the successful management of a 99-year-old female lymphoma patient with a strong wish for active treatment to improve quality of life and prolong survival past her 100th birthday. This case demonstrates that cancer treatment in the extreme elderly is possible and highlights the need for a formalized treatment plan based on geriatric assessment, frank discussion with patients and families, and defined goals of therapy.